PERAN PERTANIAN ORGANIK DALAM SISTEM KETAHANAN PANGAN: TINJAUAN DARI LITERATUR GLOBAL - Rita Hayati (CV. Adiba Aisha Amira, 2025)
Organic farming is one of the strategic approaches in supporting a sustainable global food security system. By prioritising environmentally friendly principles, organic farming reduces the use of pesticides and synthetic fertilisers, maintains soil health, and enhances biodiversity in agricultural land. Global literature indicates that this system not only provides healthy and nutrient-rich food but also contributes to climate change mitigation and farmer economic empowerment through product diversification and access to premium markets. However, organic agriculture still faces challenges such as lower productivity, high certification costs, and limited market access and technical knowledge among farmers. Policy support, technological innovation, and public education are key to optimising the role of organic farming in achieving fair, healthy, and sustainable food security in the future.